What lessons for economic development can we draw from the Champagne fairs? - Jeremy Edwards; Sheilagh Ogilvie (Center for Economic Studies and ifo Institute (CESifo), 2011)
The medieval Champagne fairs are widely used to draw lessons about the institutional basis for long-distance impersonal exchange. This paper re-examines the causes of the outstanding success of the Champagne fairs in mediating international trade, the timing and causes of the fairs' decline, and the institutions for securing property rights and enforcing contracts at the fairs. It finds that contract enforcement at the fairs did not take the form of private-order or corporative mechanisms, but was provided by public institutions. More generally, the success and decline of the Champagne fairs depended crucially on the policies adopted by the public authorities.
Keywords: N43; N73; O17; 330; legal system; medieval Europe; trade; private-order institutions; community; responsibility system; Außenhandelsgeschichte; Messe; Vertrag; Rechtsordnung; Institutionalismus; Mittelalter; Westeuropa